2023
DOI: 10.3390/foods12152955
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Antioxidant and Antibacterial Films Based on Potato Starch Incorporating Viola odorata Extract to Improve the Oxidative and Microbiological Quality of Chicken Fillets during Refrigerated Storage

Abstract: In this research, the antioxidant and antibacterial activities of active films based on potato starch containing Viola odorata extract (VOE) were investigated both in vitro and in chicken fillets. The VOE was added to the starch film formulation at 0, 1, 2, and 3% (w/v). The results showed that by increasing the extract level, the total phenol content and antioxidant and antibacterial activity of the films against Escherichia coli, Staphylococcus aureus, and Salmonella typhimurium improved remarkably. The resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…In film packaging testing, OP measures how easily oxygen molecules pass through the material. A lower OP value signifies better prevention of oxygen passage, which is crucial for preserving product quality by minimizing processes such as oxidation and spoilage [ 42 ]. The results showed that the OP responses were observed between 5.17 × 10 −8 to 3.20 × 10 −7 g/ms.…”
Section: Resultsmentioning
confidence: 99%
“…In film packaging testing, OP measures how easily oxygen molecules pass through the material. A lower OP value signifies better prevention of oxygen passage, which is crucial for preserving product quality by minimizing processes such as oxidation and spoilage [ 42 ]. The results showed that the OP responses were observed between 5.17 × 10 −8 to 3.20 × 10 −7 g/ms.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in pH level of the meat during storage at a temperature of 6 • C was greater than at a temperature of 2 • C, and on the 8th day of storage reached the level of 6.89 ± 0.10. The production of lactic acid bacteria and the accumulation of alkaline components produced by psychrotrophic bacteria and the autolytic activity of the autochthonous enzymes may be the main reason for the change in pH during storage [59]. The increase in pH level of the meat during storage may be caused by the activity of microorganisms developing in the meat, which have the ability to produce enzymes catalysing the process of deamination of amino acids, which, consequently, causes the formation of nitrogenous bases and ammonia [26,59,60].…”
Section: Resultsmentioning
confidence: 99%
“…45 A similar trend was observed while incorporating the VOE in the potato starch film at different concentrations. 72 The WVP value significantly decreased from 5.7 to 6.6 × 10 −4 g m −1 s −1 Pa −1 on the incorporation of VOE at 3% concentration due to crosslink formation between the starch polymer, plasticizer, and phenolic groups of VOE. Furthermore, the TSP film with added BLPs showed a significantly lower WVP value as compared to the neat TSP film.…”
Section: Barrier Propertiesmentioning
confidence: 93%
“…Moreover, the EAB of the film was found to have increased from 11.09 to 12.39% due to the weakening of intermolecular forces caused by the phenolic compounds of VOE. 72 Generally, for the protection of packaged food from external forces, the packaging material must exhibit a good TS, EAB, and resistance to puncture. This enables the loss-free distribution of packaged food products during storage and transportation by providing a significant level of protection.…”
Section: Mechanical Propertiesmentioning
confidence: 99%